Designing a Sumatran Tiger Conservation Illustrated Book for Children Aged 8–9 Years by Forum HarimauKita - Eki Yazid Fahmi; Gilang Cempaka (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Paramadina, 2026)
The Sumatran tiger (Panthera tigris sondaica) is an endemic species of Indonesia currently classified as Critically Endangered, with fewer than 600 individuals remaining in the wild. Beyond its ecological role as an apex predator that maintains ecosystem balance, the tiger also holds significant cultural value within Sumatran communities. However, conservation education media specifically designed for elementary school children remain limited. This study aims to design an illustrated conservation book about the Sumatran tiger for children aged 8–9 years, who are in the concrete operational stage and highly responsive to visual learning media. Unlike previous studies that discuss children’s illustration or environmental literacy separately, this research integrates ecological content, local wisdom narratives, and a research-based design approach within a unified visual communication framework. The study employs a qualitative approach using research-based design, conducted through literature review, in-depth interviews, and document analysis. The collected data were analyzed using thematic analysis and translated into the book’s visual concept. The result is an illustrated book combining adventure storytelling, anthropomorphic character design, and local cultural elements. This research contributes to the field of Visual Communication Design by proposing a conservation-based illustrated book design model and supporting early environmental education for children.